Correlations between neutrophil to lymphocyte ratio, blood eosinophils and clinical characteristics in chronic obstructive pulmonary disease - Chis, Ana Florica; Pop, Carmen Monica (Medicine and Pharmacy Reports, 2019)
Background and aims. Chronic obstructive pulmonary disease (COPD) is currently the third leading cause of death worldwide, with increasing mortality and morbidity. The neutrophil to lymphocyte ratio (NLR) and blood eosinophils level (EOS) represent biomarkers of inflammation in various diseases, with current research in the field of COPD. The aim of this study was to determine correlations of NLR and EOS with certain characteristics of COPD in a group of patients without major comorbidities. Methods. We conducted an observational study on COPD patients admitted to the Clinical Hospital of Pneumology in Cluj-Napoca, Romania. The smoking history, body mass index (BMI), NLR, EOS, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and the arterial partial pressure of oxygen (PaO2) were determined. Functional assessment consisted of spirometric and BODE index determinations. The duration of hospitalization was expressed as the length of stay (LOS). The patients were divided into 3 subgroups: active smokers (AS), former smokers (FS) and never smokers (NS). Results. No significant differences between AS and FS were found when age, airway obstruction, BODE index, PaO2, ESR and CRP were considered. The NLR was higher in AS versus FS (p=0.035), while EOS was lower in AS group (p=0.061). COPD patients with ≥300EOS/μL had lower CRP, ESR levels and NLR compared to those with eosinophilia˂300/ μL (p=0.020, p=0.009 and p=0.007, respectively). With a threshold of 3.5 for NLR, patients with lower NLR had lower CRP values (p=0.05). COPD patients with higher NLR had significant lower EOS levels (p=0.018). Overall, the NLR and EOS were not correlated with the investigated characteristics (p˃0.05), but intragroup analysis (based on smoking status) revealed correlations with ESR (p=0.0001), CRP (p=0.053), BODE index (p=0.029) and LOS (p=0.042). Conclusions. AS have higher NLR and lower EOS lelvels versus FS. COPD patients with higher EOS level have lower CRP, ESR and NLR. In AS, EOS level is positively correlated with BODE index and negatively correlated with NLR.